DEVELOPING STUDENTâ€™S MENTAL HEALTH LITERACY THROUGH PODCAST - Suryahadikusumah, Ahmad Rofi; Harum, Akhmad (Program Studi Bimbingan dan Konseling Universitas Tunas Pembangunan Surakarta, 2024)
College students and youth at their age are more susceptible to mental health problems. That has increased the need for mental health information in recent years. However, often the information received is not necessarily valid. Thus, education regarding mental health literacy is also needed. Podcasts are an alternative mental health service in the digital era. The research aims to prove the effectiveness of podcasts as a medium for developing mental health literacy. This study uses a quasi-experimental method to test the effectiveness of the podcast content entitled â€œNgomongin Diriâ€ Podcast. The research design was carried out with a one-group pre-test and post-test design. The research population was BKI UIN Sultan Maulana Hasanuddin Banten's third-semester students. Samples were taken at random at 20% of the population, and 30 people were obtained as samples. Research data regarding mental health literacy was obtained using a mental health literacy questionnaire which refers to the construct from Jorm, which consists of three domains: Knowledge, Believe, and Resource. The study results show that Podcasts are proven effective media for developing mental health literacy. The role of podcasts in increasing mental health literacy is psycho-educational media, mental health promotion, and a resource for learning coping skills.